2006
DOI: 10.1002/cncr.21921
|View full text |Cite
|
Sign up to set email alerts
|

Selecting patients for breast‐conserving therapy

Abstract: Objective Urgent evaluation and treatment of transient ischemic attack (TIA) patients in a dedicated TIA clinic may reduce the 90‐day stroke risk by 80%. ABCD2 (Age, Blood pressure, Clinical features, Duration, Diabetes) score and magnetic resonance imaging abnormalities help to identify patients at high risk of stroke. Our aim was to determine whether the use of transcranial Doppler (TCD) examination on arrival at the TIA clinic yields additional information that facilitates the identification of patients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The reported risks of tumour-positive resection margins vary between 18 and 63% and appear to be higher than the risk for patients with ductal carcinoma [8-10, 20, 21]. However, these findings were not confirmed in a recent study by Morrow et al, who found that patients with ILC did not require more operations to obtain negative margins than those with ductal carcinoma, after controlling for age and stage [22].…”
Section: Discussionmentioning
confidence: 99%
“…The reported risks of tumour-positive resection margins vary between 18 and 63% and appear to be higher than the risk for patients with ductal carcinoma [8-10, 20, 21]. However, these findings were not confirmed in a recent study by Morrow et al, who found that patients with ILC did not require more operations to obtain negative margins than those with ductal carcinoma, after controlling for age and stage [22].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ILC frequently have higher rates of involved margins, with some reports in excess of 50%, 26 , 27 and conversion to mastectomy after BCS has been reported as between 16% and 48% of cases. 28 - 30 This is partly due to the underestimation of tumour size with standard imaging modalities, mainly due to the lack of a desmoplastic reaction for ILC. Preoperative assessment with MRI has been shown to improve size estimation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Conversion to mastectomy after breast-conserving surgery (BCS) has been reported in 16-48%. 1,[3][4][5] Mammography, ultrasound and MRI are all used in assessing the extent of ILC. Whilst mammography has primarily served as a screening test, it has limited potential in young patients with dense breasts.…”
Section: Introductionmentioning
confidence: 99%